2022
DOI: 10.1002/1878-0261.13210
|View full text |Cite
|
Sign up to set email alerts
|

Development of a miRNA‐based classifier for detection of colorectal cancer molecular subtypes

Abstract: Previously, colorectal cancer (CRC) has been classified into four distinct molecular subtypes based on transcriptome data. These consensus molecular subtypes (CMSs) have implications for our understanding of tumor heterogeneity and the prognosis of patients. So far, this classification has been based on the use of messenger RNAs (mRNAs), although microRNAs (miRNAs) have also been shown to play a role in tumor heterogeneity and biological differences between CMSs. In contrast to mRNAs, miRNAs have a smaller siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…As a type of noncoding RNA, miRNAs participate in a variety of cellular biological processes and can combine with the 3ʹUTR and regulate the expression of target genes [50,51]. It is acknowledged that the controlled expression of miRNAs is indispensable for normal cells, while the aberrant expression of miRNAs may lead to diseases, including cancers [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…As a type of noncoding RNA, miRNAs participate in a variety of cellular biological processes and can combine with the 3ʹUTR and regulate the expression of target genes [50,51]. It is acknowledged that the controlled expression of miRNAs is indispensable for normal cells, while the aberrant expression of miRNAs may lead to diseases, including cancers [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The Consensus Molecular Subtypes (CMSs) have implications for our understanding of tumor heterogeneity and the prognosis of patients (Guo et al, 2021;Zhong et al, 2021). So far, the classification has been widely based on the use of messenger RNAs (mRNAs), although miRNAs have been shown to play vital roles in tumor heterogeneity and biological differences between CMSs (Lu et al, 2005;Adam et al, 2022). In contrast to mRNAs, miRNAs have a smaller size and increased stability, facilitating their detection and thus became an important matter for biomarker researchers.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs expression data (miRNA-Seq) from TCGA-COAD were classified using miRaCl classifier [ 12 ] available at Github/rsmadam/CMS-miRaCl. Subtype association between miRNA and mRNA classification was determined using Chi-square test (χ 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This can be an important advance, since it would allow the search of the relevant miRs in serum/plasma of patients and their classification, as other authors have reported for pancreatic adenocarcinoma [ 11 ], without the need to obtain biopsies or fragments of the tumor, facilitating real-time analysis of the course of the disease and of the response to the treatment. A just released report, develops a miR classifier using supervised analysis to predict four miR subtypes assigned from the four mRNA CMS subtypes [ 12 ]. Using in silico machine learning the study of Adam et al [ 12 ] converts the four mRNA-CMS subtypes to four miR-subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation